The Impact of Political Dynamics on Stock Prices During Indonesia’s 2024 Presidential Election - Gina Sonia; Rohmini Indah Lestari; Ardiani Ika (Economics and Digital Business Review, 2026)
This study aims to determine the development and changes in Indonesian stocks due to political turmoil, namely the presidential election. Political events such as presidential elections have the potential to have good or bad impacts on economic stability and the investment climate. This study uses an event study approach in analyzing the abnormal return of the LQ45 index on the Indonesia Stock Exchange before, during and after the General Election in 2024. In this study, the population studied was the LQ45 Index on the Indonesia Stock Exchange in the period February-July 2019. Sampling in this study used the Saturated Sampling technique, where all members of the population were sampled. The number of samples in this study is the same as the population, which is 45 companies. The results of the study show that there are indications of statistically and economically significant abnormal returns around the voting period carried out simultaneously on February 14, 2024, especially a positive spike after D-day, which was then followed by a gradual decline, there is a difference in abnormal returns between before, during, and after the 2024 election voting, there is an economically significant abnormal return, especially after the announcement of the election results, which was then followed by market stabilization, there is a difference in abnormal returns between before, during, and after the announcement of the 2024 election results.